PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, PROMOSI DAN MUTASI TERHADAP KINERJA KARYAWAN (Studi Kasus di Koperasi Karya Usaha Madiri Syariah Cabang Sagaranten Sukabumi) - Agung Mubarok; Tubagus Rifqy Thantawi; Hasbi Ash Shiddieqy (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
ABSTRACT Performance is the result of work and work behavior that has been achieved in completing the tasks and responsibilities given within a certain period. (Kasmir, 2016: 182). Increased individual performance (individual performance) is likely to increase the company's performance (corporate performance) because the two have a close relationship. This study aims to determine the effect of leadership style, motivation, promotion and transfer on the performance of employees of KKUMS Sagaranten Sukabumi Branch. The type of research used is quantitative with a survey approach and uses multiple linear analysis because the independent variable consists of more than one. This study is directed to analyze and describe in-depth data about the influence of leadership style, motivation, promotion and transfer on employee performance. The results of this study conclude that: First, based on the results of the tests carried out, the influence of leadership style variable (X1) partially shows that there is a significant effect on employee performance variables because 0.858> 0.05 and tcount 0.186 < ttable 2.44691; Second, based on the results of the tests carried out, the motivation variable (X2) partially shows that there is a significant influence on the employee performance variable because 0.197>0.05 and the tcount -1.449<ttable 2.44691; Third, Based on the test results, the promotion variable (X3) partially shows that there is a significant effect on the employee performance variable because it is 0.693>0.05 and the tcount value is -4.14 <ttable 2.44691; Fourth, based on the results of the tests carried out, the mutation variable (X4) partially shows that there is no effect on the employee performance variable because it is 0.048 <0.05 and the value of tcount is 2.470>ttable 2.44691; and fifth, the independent variables together (simultaneously) have no effect on the dependent variable because 7.956>4.12 with a significance level of 0.14 because the significance level is> than 0.05, then this regression model cannot be used for employee performance variables. . Keywords: Leadership Style, Motivation, Promotion, Transfer, Performance